The Comparison of Serum Malondialdehyde Level Between H. pylori Positive and H. pylori Negative Gastritis Patients - Laura Dairi; Gontar Alamsyah Siregar; Taufik Sungkar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Background: Helicobacter pylori is the most common cause of chronic gastritis in the world, meanwhile gastritis caused by non-steroidal anti-inflammatory drugs (NSAIDs) is the most encountered type of gastritis.Increased free radicals caused by Helicobacter pylori can cause damage in gastric mucous. Tissue damage due to free radicals can be examined by measuring malondialdehyde compound. There are many studies thatproves the increased malondialdehyde in gastritis, but those studies commonly done in animal experimentation and malondialdehyde examination in gastric mucous.Method: This is a cross-sectional study of 40 dyspepsia patients who came to endoscopic unit of Adam Malik General Hospital Medan and networking hospitals by using Rome III criteria. Further examination with gastroscopy and biopsy was done to determine gastritis. H. pylori examination was done by using Campylobacterlike organism test (CLO) test. Serum malondiasldehyde level was examined with high performance liquid chromatography (HPLC) method.Results: From total of 40 patients,24 (60%) were men and 16 (40%) were women with an average age of 47years, the majority of the ethnic was Bataknese (57.5%). From 20 patients with H.pylori (+), the average levelof malondialdehyde was 1.58 umol/mL while in 20 other patients with H. pylori (-), malondialdehyde level was 1.19 umol/mL with p value 0.013.We found the mean serum levels of malondialdehyde was higher in H. pyloripositive gastritis than H. pylori negative.Conclusion: Serum Malondialdehyde level was significantly higher in patient with positive H. pylori gastritiscompared to H. pylori negative gastritis.